English Present Perfect Tense in ESP Context: The Case of Paramedical English in Iran - SOLATI, AKBAR (The journal of contemporary issues in business and government, 2021)
This study sets out to investigate the possible effects of interlingual and intralingual interference strategies as significant issues in causing difficulties in the acquisition of the English present perfect tense by paramedical students. To achieve the objectives, a multiple- choice test was administered to 30 first year paramedical students to assess their knowledge of rules governing the use of English present perfect tense. The results imply that the intralingual interference strategies seemed to be the cause of the most errors. Instead, the interlingual interference strategies might cause some other errors. It seems that the common cause of the errors in this study is that thepresent perfect tense forms and their time references in English and Persian are not the same. A tense form has more than one time reference; or conversely, one time reference is represented by more than one tense form.